Institutions and attribution of responsibility outside the electoral context: a look at French semi-presidentialism. Issue 2 (4th November 2015) - Turgeon, Mathieu; Bélanger, Éric
Abstract : Some institutional arrangements may be undesirable for democracy by obscuring which political actors are to be held responsible for failed or successful policies and bad or good macroeconomic performances. Much of the work in the area has focused on whether institutions affect the 'clarity of political responsibility' and the ability of voters to punish or reward, in turn, governments and elected officials. Not much has been said, however, about the assignment of responsibility outside the electoral context, for a broad range of policy areas. This paper explores these questions in the context of French semi-presidentialism. It demonstrates that the French public is surprisingly quite responsive to the demands imposed by their political system by adjusting reasonably well their evaluations of both actors of the executive in light of major political events and changes in the economic conditions when the circumstances clearly indicate which of the two is 'in charge'. At other times, however, this particular institutional arrangement obscures instead political responsibility.